Love the job... or the patient? Task vs. mission-based motivations in health care - Sheheryar Banuri; Philip Keefer; Damien De Walque (Inter-American Development Bank (IDB), 2018)
A booming literature has argued that mission-based motives are a central feature of mission-oriented labor markets. This paper shifts the focus to task-based motivation and finds that it yields significantly more effort than mission-based motivation. Moreover, in the presence of significant task motivation, mission motivation has no additional effect on effort. The evidence emerges from experiments with nearly 250 medical and nursing students in Burkina Faso. The students exert effort in three tasks, from boring to interesting. In addition, for half of the students, mission motivation is present: their effort on the task generates benefits for a charity. Two strong results emerge. First, task motivation has an economically important effect on effort. Second, mission motivation increases effort, but only for mundane tasks and not when the task is interesting. Moreover, even for mundane tasks, the effects of mission motivation appear to be less than those of task motivation.
Keywords: C91; H83; J45; 330; civil service; extrinsic motivation; intrinsic motivation; performance; public sector reform